Environmental impacts on second-generation biofuel production from lignocellulosic biomass - Mishra R.K.; Misra Y.; Prasanna Kumar D.J.; Sankannavar R.; Kumar P. (My University, 2025)
The increasing demand for renewable energy sources has led to development of second-generation biofuels derived from lignocellulosic biomass. However, producing these biofuels can have environmental impacts that must be considered. The production of second-generation biofuels involves the conversion of biomass into biofuels such as ethanol, butanol and biogas. The process typically involves pretreatment, hydrolysis, fermentation and distillation. These processes can have significant environmental impacts, including greenhouse gas emissions, land use change, water consumption and air pollution. Using biomass for energy production can also emit particulate matter, nitrogen oxides and sulfur dioxide, which adversely impact the environment. To minimize these detrimental environmental effects, adopting sustainable practices such as using sustainable feedstock, efficient conversion processes and renewable energy sources to power the production process is essential. Additionally, recycling waste streams and using by-products can minimize waste generation and reduce the environmental footprint of biofuel production. The production of second-generation biofuels from lignocellulosic biomass has the potential to provide a sustainable source of renewable energy. This book chapter explores the environmental impacts of second-generation biofuel production from biomass. This chapter also provides mitigation strategies against these impacts and briefly overviews the future outlook and challenges. © 2025 Elsevier Ltd. All rights reserved.